ANALISIS MOTIVASI KERJA KARYAWAN BAGIAN PEMASARAN PT. GLOBAL MITRA PRIMA - NGAJUDIN NUGROHO; EFFENDI CHUA; ARWIN .; WONG PONG HAN; WILINNY . (LP2MTBM MAKARIOZ, 2019)
The objective of this research is to analyze the motivation method applied on Marketing Staff at PT Global Mitra Prima,Medan. The research method using descriptive qualitative, data collection method using structure interview, and samplingtechnique are using purposive sampling. The result of this research conclude the marketing staff at PT Global Mitra Primastated that they rarely get compliment, promotion, pay hike from leader of the company. Marketing staff at PT Global MitraPrima also says that facilities provided by the company really help them in doing their jobs, the enviroment in the company isvery comfortable, their co-worker attitude very good in this company. They have a good relationship as a colleague in thecompany. The company also providde the complete facilities such as Car for company needs, computer, air conditioner, thecomplete stationary, table and chair, printer, photocopy machine, and wi-fi.